MILITARY TERMINOLOGY AND ITS IMPACT ON CIVILIAN LANGUAGE - Shokhnoza Panjievna Imomova (International Engineering Journal For Research & Development, 2023)
Military terminology has been known to affect civilian language in various ways. This paper aims to discuss the impact of military terminology on civilian language and the reasons for its widespread usage. The paper uses various studies to provide insights into how the military lexicon has influenced the language used by civilians. Moreover, it discusses the reasons for the increasing usage of military terminology in everyday language and its effects on communication.